Analysis Of Factors Affecting The Use Of FAM Behavior (Food Additional Material) In Food Traders Group In The Environment Ponorogo All District Market South Region - Anwar, Muhammad Choirul; Nurwijayanti, Nurwijayanti; Farida, Siti (Journal of Global Research in Public Health, 2019)
Food Additives (FA) or often called Food Additional Material (FAM) are ingredients added to food to influence the nature or shape of food. Addition of additives to food has a certain dose because food additives can cause health hazards. The purpose of this study was to determine the analysis of factors that influence the behavior of using FAM in the food traders group in the market area of ​​the South Region Ponorogo Regency. This research is an observational analytic study. The population of this research is all traders in the market environment of the South Region Ponorogo Regency. The sampling technique used is Stratified Random Sampling. Samples taken were 105 respondents. The independent variable is knowledge and attitude, the dependent variable is the behavior of traders. Data is collected by questionnaire instruments and processed using editing, coding, scoring and tabulating then statistical tests using logistic regression test data analysis with α = 0.05. From the ordinal regression statistical test, the p-value value in the knowledge factor p = 0.005 <0.05, on the attitude factor p = 0.000 <0.05. The magnitude of influence is indicated by the value of Estimate. Knowledge variable with 2.743, while attitude variable with estimate value 26.911. Based on the results of the estimate value or the magnitude of the largest or dominant influence lies in the attitude variable with an estimated value of 26.911. So it can be concluded that the most dominant factor influencing behavior is an attitude factor with an effect of 26,911 times. In the use of food additives for the processing of food to be sold it must be appropriate and correct according to the applicable dosages and conditions.